ERas Enhances Resistance to Cisplatin-Induced Apoptosis by Suppressing Autophagy in Gastric Cancer Cell - Tian, Huajian; Wang, Wenjun; Meng, Xiao; Wang, Miaomiao; Tan, Junyang; Jia, Wenjuan; Li, Peining; Li, Jianshuang; Zhou, Qinghua (Frontiers in Cell and Developmental Biology, 2020)
Gastric cancer, a common type of malignant cancer, remains the fifth most frequently diagnosed cancer and the third leading cause of cancer-related deaths worldwide. Despite developments in the treatment of gastric cancer, the prognosis remains poor. ERas (embryonic stem cell-expressed Ras), a novel member of the Ras protein family, has recently been identified as an oncogene involved in the tumorigenic growth of embryonic stem cells. A recent study reported that ERas is expressed in most gastric cancer cell lines and gastric cancer specimens, and it promotes tumorigenicity in gastric cancer through induction of the EMT and activation of the PI3K/AKT pathway. Here, we found that ERas blocked autophagy flux in BGC-823 and AGS gastric cancer cells, which may occur through activation of the AKT/mTOR signaling pathway. Moreover, ERas overexpression suppressed cisplatin-induced apoptosis, and rapamycin treatment significantly attenuated ERas-mediated cisplatin resistance in gastric cancer cells. These data suggest that ERas may be a potential therapeutic target to improve the outcomes of gastric cancer patients by regulating the autophagy process.